Antibiofilm Efficacy of Luteolin Against Single and Dual Species of Candida albicans and Enterococcus faecalis - Fu, Yuting; Wang, Wenjing; Zeng, Qiao; Wang, Ting; Qian, Weidong (Frontiers in Microbiology, 2021)
Candida albicans and Enterococcus faecalis biofilm-associated infections have been a huge challenge to the medical community. However, the efficacy of natural products against mixed biofilms of C. albicans and E. faecalis still remains largely unexploited. The aim of this study was to evaluate the efficacy of luteolin against planktonic cell growth, adhesion and biofilm formation of C. albicans and E. faecalis in single and mixed cultures in vitro. The results showed that minimum inhibitory concentrations of luteolin against planktonic cells of C. albicans, E. faecalis and mixed cultures were 32 μg mL-1 and 64 μg mL-1, respectively. The results displayed that a remarkable variation in biofilm biomass, viability, structure, composition of single and dual-species biofilms formed by mono- and dual-species of C. albicans and E. faecalis in the presence of luteolin was confirmed by mainly crystal violet staining assay (CVSA), optical microscope, field emission scanning electron microscope (FESEM) and confocal laser scanning microscope (CLSM). The tolerance of luteolin-treated single and dual-species biofilms to antibiotics was found to obviously decreased, and the loss of biofilm matrix components (mainly polysaccharides and proteins) was revealed by CLSM. Moreover, luteolin was effective at inactivating biofilm cells, as well as destructing preformed biofilm structures by single and dual-species by CVSA, FESEM and CLSM. Collectively, these data indicate the potential of luteolin as a promising antibiofilm agent for the therapeutic management of biofilm-related infections induced by single and dual-species of C. albicans and E. faecalis.